Organisational culture and innovation: testing the Schein Model at a private university in Zimbabwe - William Makumbe; Yollanda Yeukayi Washaya (Cogent Business & Management, 2022)
Universities are now regarded as strategic actors in the knowledge economy which is mainly anchored on innovation. As organisational culture is considered a key enabler of innovation, university managers must know the specific organisational culture features that can enhance innovation. However, studies that test the relationship between organisational culture and innovation are limited in universities especially in developing countries. This is especially true in Africa, where higher education research barely exists. In light of this, the purpose of this study was to use the multi-layered Schein Model to test the relationship between organisational culture and innovation at a private university in Zimbabwe. The study adopted the survey method and collected data from 250 academics using the SurveyMonkey platform. Data was analysed using the Structural Equation Modelling. Results revealed that values and artifacts were positively related with innovation. Norms had a negative relationship with innovation. The results of this study facilitate the allocation of resources towards specific organisational culture characteristics that can support innovation in African universities.
Keywords: 650; innovation; organisational culture; artifacts; Schein Model; Zimbabwe